Benign Bone Tumors When They Coexist with Common Orthopaedic Conditions - Hasan, Khalid; Nguyen, Duc M.; Conway, Sheila A. (The Journal of Knee Surgery, 2019)
Benign and malignant bone tumors around the knee can be encountered with concomitant orthopaedic disease. As such, it is important to recognize these oncologic processes that may impact or alter the routine treatment of more common orthopaedic processes. Frequently, these rare oncologic conditions are discovered only through the evaluation of acute injuries as in the setting of fractures or sports injuries. Other times, they are encountered when evaluating chronic entities, such as arthroplasty. This article aims to provide general guidelines and management strategies for benign bone tumors when they coincide with common orthopaedic conditions around the knee.
Keywords: orthopaedic; benign; tumors; knee; coexist; common knee problems; arthroplasty; sports injuries; fractures